Spectrum Paint Sdn. Bhd. / Norrizah Bakar ... [et al.] - Bakar, Norrizah; Ali, Noorqamarina; C. Wan Zakaria, Cik Wan Norhidayu; Ismail, Nor Azlina; Mat Hashim, Siti Sarah (2002)
Our company is distributing paint to customer by retailers and contractor as the most users. We are supplying paint with various colours and brands that will fulfil the customer’s demad or interested. We choose to supply 5 liters, 7 liters and 18 liters paint because these quantities are usually use by the customers. The brands that we supply are Nippon, Sissons, Glidden and Dulux.